The Influence of Solomonâs Story in the Quran on Hafiz Sonnet 216 - Ali Nazari (دراسات في اللغة العربيّة وآدابها)
The holy Quran exerted great influence on Hafiz Sonnets. Sometimes this influence has been symbolic and open to different poetic and figurative interpretations. Hafiz has adopted Quranic words and expressed them in beautiful ways with strong effect. It seems there is a high amount of correspondence between Hafizâs Sonnet 216 and the story of Solomon in the Quran (Surah Naml) in wording, notions, themes and artistic and symbolic expressions. Clearly, Hafiz based his poem on this Quranic story and Zemakhshariâs interpretation of Verse 44 in Naml. Fairy, Saba Queen, dissatisfaction of Jens as to Solomonâs marriage to Saba Queen are among the themes Hafiz incorporated into his poem and presented in an artistic sonnet. For example, he took ânazarâ (glance, look) from Solomonâs words and used it in a phrase in his poem to refer to âwise wordsâ and âwisemanâ. It is difficult to discover this connection at first glance. However, this technique makes Hafizâs poetry very interesting and enjoyable to read.